Responsiveness of pituitary to galanin throughout the reproductive cycle of male European sea bass (Dicentrarchus labrax) - Pinto, P. (2019)
The neuropeptide galanin (Gal) is a putative factor regulating puberty onset and reproduction through its actions on the pituitary. The present study investigated the pituitary responsiveness to galanin and the patterns of galanin receptors (Galrs) expression throughout the reproductive cycle of two years old male European sea bass (Dicentrarchus labrax), an important aquaculture species. Quantitative analysis of pituitary and hypothalamus transcript expression of four galr subtypes revealed differential regulation according to the testicular developmental stage, with an overall decrease in expression from the immature stage to the mid-recrudescence stage. Incubation of pituitary cells with mammalian 1-29 Gal peptide induced significant changes in cAMP concentration, with sensitivities that varied according to the testicular development stages. Furthermore 1-29 Gal was able to stimulate both follicle stimulating hormone (Fsh) and luteinizing hormone (Lh) release from pituitary cell suspensions. The magnitude of the effects and effective concentrations varied according to reproductive stage, with generalized induction of Fsh and Lh release in animals sampled in January (full spermiation). The differential expression of galrs in pituitary and hypothalamus across the reproductive season, together with the differential effects of Gal on gonadotropins release in vitro strongly suggests the involvement of the galaninergic system in the regulation the hypothalamus-pituitary-gonad axis of male sea bass. This is to our knowledge the first clear evidence for the involvement of galanin in the regulation of reproduction in non-mammalian vertebrates. (C) 2017 Elsevier Inc. All rights reserved.